Bifidobacterium breve BBG-001 in very preterm infants: a randomised controlled phase 3 trial. - Costeloe, K; Hardy, P; Juszczak, E; Wilks, M; Millar, M (Elsevier, 2015)
Background Probiotics may reduce necrotising enterocolitis and late-onset sepsis after preterm birth. However, there has been concern about the rigour and generalisability of some trials and there is no agreement about whether or not they should be used routinely. We aimed to test the eff ectiveness of the probiotic Bifidobacterium breveBBG-001 to reduce necrotising enterocolitis, late-onset sepsis, and death in preterm infants. Methods In this multicentre, randomised controlled phase 3 study (the PiPS trial), we recruited infants born between 23 and 30 weeks’ gestational age within 48 h of birth from 24 hospitals in southeast England. Infants were randomly assigned (1:1) to probiotic or placebo via a minimisation algorithm randomisation programme. The probiotic intervention was B breveBBG-001 suspended in dilute elemental infant formula given enterally in a daily dose of 8·2 to 9·2 log10 CFU; the placebo was dilute infant formula alone. Clinicians and families were masked to allocation. The primary outcomes were necrotising enterocolitis (Bell stage 2 or 3), blood culture positive sepsis more than 72 h after birth; and death before discharge from hospital.All primary analyses were by intention to treat. This trial is registered with ISRCTN, number 05511098 and EudraCT, number 2006-003445-17. Findings Between July 1, 2010, and July 31, 2013, 1315 infants were recruited; of whom 654 were allocated to probiotic and 661 to placebo. Five infants had consent withdrawn after randomisation, thus 650 were analysed in the probiotic group and 660 in the placebo group. Rates of the primary outcomes did not differ significantly between the probiotic and placebo groups. 61 infants (9%) in the probiotic group had necrotising enterocolitis compared with 66 (10%) in the placebo group (adjusted risk ratio 0·93 (95% CI 0·68–1·27); 73 (11%) infants in the probiotics group had sepsis compared with 77 (12%) in the placebo group (0·97 (0·73–1·29); and 54 (8%) deaths occurred before discharge home in the probiotic group compared with 56 (9%) in the placebo group (0·93 [0·67–1·30]). No probiotic-associated adverse events were reported. Interpretation There is no evidence of benefi t for this intervention in this population; this result does not support the routine use of B breve BBG-001 for prevention of necrotising enterocolitis and late-onset sepis in very preterm infants.